2019
DOI: 10.1111/crj.13096
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of smoking cessation in smokers with COPD and nocturnal oxygen desaturation: Functional analysis

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) is the fourth cause of mortality and it’s frequently associated with breathing sleep disorders.ObjectiveThe aim of the study is to point out the benefit of smoking cessation over three months in terms of improvement of respiratory functional variables.MethodsA retrospective analysis was performed evaluating the impact of smoking cessation on 145 patients with COPD and nocturnal oxygen desaturation. For this purpose, for all patients, overnight pulse oxym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 21 publications
1
36
0
2
Order By: Relevance
“…Furthermore, our pilot data should be confirmed in a larger number of subjects who should provide at least a pair of samples before and after smoking cessation. If future studies confirm our observation, it should be mentioned that no effect or a small effect on urine miRNAs is not in contrast with the well-established benefits of smoking cessation [ 32 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, our pilot data should be confirmed in a larger number of subjects who should provide at least a pair of samples before and after smoking cessation. If future studies confirm our observation, it should be mentioned that no effect or a small effect on urine miRNAs is not in contrast with the well-established benefits of smoking cessation [ 32 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 67%
“…Then the dosage was 0.5 mg twice a day for four days. Lastly, the dosage was increased up to 1 mg twice per day [ 32 ]. A starting dose of bupropion was 150 mg taken once a day for three days and then increased to 150 mg taken twice a day.…”
Section: Methodsmentioning
confidence: 99%
“…49 Smoking cessation has been effective in improving several clinical and physiologic parameters in COPD. 50 It may be prudent to design studies which can determine the true order of progression of changes and develop optimal smoking cessation strategy and medications (e.g., antifibrotics) for overlapping therapeutic effects across this spectrum of pathologies. 45,51 After more than a decade of research in CPFE, the prognostic implication of comorbid emphysema in IPF remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that a longer duration of COPD and higher SGRQ score were relevant to good adherence to smoking cessation treatment. Previous studies [32][33][34] found the relationship between COPDrelated features and the efficacy of smoking cessation. For example, the study by Tøttenborg et al found that the higher GOLD stage, the better the efficacy of smoking cessation.…”
mentioning
confidence: 99%